Investigation on the Anthropometric and Physiological Features Of Alpine Discipline and Nordic Discipline Turkish National Ski Teams - Vahdet Alaeddinoğlu; İsmail Kaya (ümit doğan üstün, 2016)
The aim of this study was to investigate of physical features, explosive power, and stamina and body fat percentage of youngster male skiers of Turkish National Ski Team. A total of 28 sportsmen -15 sportsmen on Nordic Discipline and 13 sportsmen on Alpine Discipline- volunteered for the study. Depending on training program of the volunteering sportsmen some physical and physiological parameters were mutually examined. The date of birth, height, weight, and the height seated and arm span also fat measurements, round measurements, length measurement, standing long jump, push-up, shuttle, and jump and grip strength values were examined. In the evaluation of the data SPSS for Windows 17 package program was used and significance degree was taken at the degree of a=0.05 and 0.01. This study showed significant differences between physical p<0.05, explosive power p<0.05, agility p<0.05, and body fat percentage.